ANALISA SPASIAL LOKASI KORIDOR KOMERSIAL DISTRO DAN BUTIK DI KOTA PONTIANAK - Nunik Hasriyanti; Andi Zulestari; Julius Judhi (TATALOKA, 2018)
Pontianak city is a service city that is now beginning to grow more rapidly. The growth of the trading sector in Pontianak City that became the center of economic activity that attracts people outside the city of Pontianak to come and conduct economic activities in the city. And of course for most citizens to do the business of trading centers like distro and boutique outlet. But the location of this shopping center is not in accordance with Pontianak City Spatial Plans because of its located at the settlements location, offices and services. The proliferation of this shopping center on the one hand raises a positive aspect for the regional income (PAD) Pontianak City, will be replaced on the other side of the negative side of the problem of congestion, lack of parking space, the number of billboards that disturb the visual of the city and change the image of an area. In this study will be evaluated the location of shopping centers distro and boutiques by using Analytic Hierarchy Process (AHP), so get the best alternative location in the selection of commercial locations for distro and boutique in the city of Pontianak. From this research, it can be concluded that the result of data calculation on various aspects that become criteria are Physical, Social, Economy and accessibility aspects where the highest hierarchy is economic aspect with the highest sub aspect is investment attraction which is the benchmark of criteria is the flow of money flow) in large numbers, crowded by Questions, resolved over the weekend, rising land prices, free of illegal levies that could be entitled to entrepreneurs / investors. Of the 10 sub-aspects of criteria for the assessment of the three corridors of the middle roads of the distro and boutiques, the results of the corridor of Jalan Gusti hamzah were superior with 9 sub-aspects with a value of 0.5253 compared with the other two corridors namely M. Yamin Street with value 0, 2555 and Jalan Danau Sentarum with value 0,2154.